Boosting power density of hydrogen release from LOHC systems by an inverted fixed-bed reactor design - Kadar, Julian; Gackstatter, Felix; Ortner, Florian; Wagner, Lisa; Willer, Miriam; Preuster, Patrick; Wasserscheid, Peter; Geißelbrecht, Michael (International Journal of Hydrogen Energy, 2024)
Hydrogen storage and transportation in form of charged Liquid Organic Hydrogen Carrier (LOHC) systems is attractive as these hydrocarbon-based carrier molecules can provide hydrogen using the existing infrastructure for fossil fuels. For hydrogen release on board of heavy-duty vehicles, however, the limited volumetric power density of the hydrogen release units was so far seen as a critical factor. Herein, we show that the power density achieved in perhydro benzyltoluene dehydrogenation in a classical fixed-bed dehydrogenation reactor can be doubled by applying an inverted multi-tubular reactor with upstream LOHC flow and hydrogen release in the reactor housing and crossflow heating through perpendicular heating tubes. The resulting power densities of up to 0.76kWH2-LHV L−1reactor-outside (with respect to the total reactor housing), and 2.34kWH2-LHV L−1reactor-inside (with respect to inner reactor volume) bring on-board hydrogen release of LOHC-bound hydrogen much closer to technical reality. This very impressive increase in power density is mainly due to the fact, that the inverted arrangement of catalyst bed and heat transfer tubes offers a much higher catalyst volume per reactor volume compared to a classical fixed-bed reactor.
CRIS-Team Scopus Importer:2024-03-01
Keywords: Dehydrogenation; Heat transfer; Hydrogen storage; LOHC; Perhydro benzyltoluene

Evaluation of a novel reactor concept for the process intensification and intelligent heat management in the hydrogenation and dehydrogenation of Liquid Organic Hydrogen Carriers - Preuster, Patrick; Wagner, Lisa; Nuß, Andreas; Geiling, Johannes; Steinberger, Michael; Bösmann, Andreas; Wasserscheid, Peter (21st World Hydrogen Energy Conference 2016, WHEC 2016, 2016)

Hydrogen Storage in a Pressure Swing Reactor – Development of a Continuous Reactor Design. - Dürr, Stefan; Wagner, Lisa; Preuster, Patrick; Wasserscheid, Peter (1st INTERNATIONAL YOUNG PROFESSIONALS CONFERENCE ON PROCESS ENGINEERING (YCOPE 2019), 2019)
Hydrogen storage via reversible catalytic hydrogenation and dehydrogenation of Liquid Organic Hydrogen Carrier (LOHC) molecules such as dibenzyltoluene, has outgrown laboratory scale setups. LOHC storage systems now are commercially available and prove to be a safe and practical solution for hydrogen storage. [1] A state of the art LOHC-system intended for hydrogen transport comprises separate hydrogenation and dehydrogenation units: One at the site of hydrogen production and another one on the site of hydrogen demand. However, it was recently shown that both reactions can be implemented in a simple one-reactor setup using only one Pt-catalyst. [2,3] Consequently, given an adequately high temperature, the reaction mode can be set to hydrogenation or dehydrogenation by applying the appropriate pressure. This provides for a highly dynamic, more cost- and energy efficient plant design for scenarios in which no transport is intended. Moving from semi-batch to continuous mode offers several advantages such as more efficient noble metal use and separate scaling of capacity and maximum input/output rate of hydrogen. In this flow-battery-like setup, capacity solely depends on tank size while maximum hydrogen flow is determined by reactor design. Thus the combination of a compact, high-performance reactor and cost-effective, refillable tanks allows highly flexible solutions for a variety of hydrogen storage and supply scenarios. To account for the reaction enthalpies of both reactions our oneReactor concept is based on a shell-and-tube heat exchanger design. Multiple catalyst containing, vertical tube reactors are employed in co- or counter-current trickle-bed mode. Since frequent change from hydrogenation to dehydrogenation mode and varying reaction times lead to differing feed compositions, a liquid loop is applied to obtain a more stable mode of operation. In this poster presentation we show the feasibility of the oneReactor-concept as well as first experimental results. Furthermore examples of system integration in both energy-storage and hydrogen supply will be discussed. [1] Preuster, P., et al. (2017). “Liquid Organic Hydrogen Carriers (LOHCs): “Toward a Hydrogen-Free Hydrogen Economy,” ACCOUNTS OF CHEMICAL RESEARCH 50 (1): 74-85 [2] Jorschick, J., et al. (2017). “Hydrogen Storage Using a Hot Pressure Swing Reactor,” ENERGY & ENVIRONMENTAL SCIENCE 10 (1): 1652-1659 [3] Jorschick, J., et al. (2018). “Operational Stability of a LOHC-based Hot Pressure Swing Reactor for Hydrogen Storage,” ENERGY TECHNOLOGY 10.1002/ente.201800499, (early access) </

Hydrogen Storage via Pressure Swing Reaction – Development and Advantages of Continuous Reactor Design - Dürr, Stefan; Wagner, Lisa; Steinberger, Michael; Geiling, Johannes; Preuster, Patrick; Oechsner, Richard; Wasserscheid, Peter (Integration of Sustainable Energy Conference, Nürnberg, 2018)

Hydrogen Storage via Pressure Swing Reaction – from Batch to Continuous Reactor Design - Dürr, Stefan; Wagner, Lisa; Preuster, Patrick; Wasserscheid, Peter (World Hydrogen Energy Conference, 2018)

Operational experience with a liquid organic hydrogen carrier (LOHC) system for bidirectional storage of electrical energy over 725 h - Geiling, Johannes; Wagner, Lisa; Auer, Franziska; Ortner, Florian; Nuß, Andreas; Seyfried, Roman; Stammberger, Florian; Steinberger, Michael; Bösmann, Andreas; Öchsner, Richard; Wasserscheid, Peter; Graichen, Knut; et al. (Journal of Energy Storage, 2023)
Hydrogen storage in liquid organic hydrogen carriers (LOHC) enables the utilization of renewable energy in different sectors. In this paper, we describe the operational experience with one single LOHC system for bidirectional electrical energy storage at the kW scale. The system includes a reactor for the hydrogenation and dehydrogenation of LOHC, as well as a fuel cell and an electrolyzer based on polymer electrolyte membrane (PEM) technology. The LOHC used is the substance pair dibenzyltoluene/perhydro-dibenzyltoluene. For dehydrogenation, the upflow operation with common discharge of liquid and gaseous product was found to be the preferred mode of operation. For hydrogenation, it was shown that stable operation is possible also with fluctuating hydrogen production from the electrolyzer. After operating the reactor for 725 h in the hot state, i.e., at temperatures above 150 ∘C, samples of the catalyst and LOHC were taken and analyzed. These showed no signs of serious degradation.
CRIS-Team Scopus Importer:2023-08-25
Keywords: Catalyst; Hydrogen storage; Liquid organic hydrogen carrier (LOHC); Operation experience; PEM electrolyzer; PEM fuel cell